Endogenous Leverage and Asset Pricing in Double Auctions - Thomas Breuer; Martin Summer; Hans-Joachim Vollbrecht (Oesterreichische Nationalbank (OeNB), 2013)
We study the trading of real assets financed by collateralized loans in an agent based model of a continuous double auction. This approach provides a complementary perspective on recent advances in the general equilibrium theory of endogenous leverage by studying a model that simultaneously describes dynamic and equilibrium properties of the market. Rather than taking prices as parametric there is an explicit price formation process which can be simulated or studied empirically. This is important because the economics of leverage is key to the understanding of financial crisis. We find that simulated double auctions converge to stable final states close to the theoretical equilibrium state. Consistent with equilibrium theory, real assets are traded at a price above fundamental value in the double auction. The equilibrium level of leverage also emerges in the simulations of the double auction.
Keywords: D53; G12; G14; C63; 330; Leverage; Asset Pricing; Double Auction; Agent Based Modeling; Kreditderivat; Allgemeines Gleichgewicht; Agentenbasierte Modellierung; Kapitalmarkttheorie; Auktionstheorie